How does self-efficacy moderate the effect of guided inquiry learning on sixth-grade students' critical thinking skills in science? - Ni Putu Sudiartini; I Nengah Suastika; Desak Putu Parmiti (Psychology, Evaluation, and Technology in Educational Research, 2025)
This study investigated the moderating role of self-efficacy in the effect of the Guided Inquiry learning model, supported by GI Worksheets, on the critical thinking skills of Grade 6 students. A quasi-experimental pre-test and post-test design was employed, involving 30 students. The findings revealed that while the Guided Inquiry model significantly improved critical thinking (β = 3.10, p < 0.05), this effect was moderated by self-efficacy (β = 0.42, p < 0.05). Students with high self-efficacy demonstrated substantially greater gains in critical thinking than their low self-efficacy peers. This suggests that the effectiveness of inquiry-based learning is contingent upon students' self-belief and psychological readiness. The study underscores the importance of fostering self-efficacy alongside the implementation of effective instructional models to optimize cognitive development in elementary science education.